ANALISIS KEMAMPUAN MEMBACA ANAK TUNARUNGU MELALUI PENDEKATAN KOMTAL DI SEKOLAH DASAR NEGERI BONTOTE’NE - Rukli Rukli; Nurjannah Nurjannah (Elementary School Teacher Education (PGSD), STKIP PGRI Sumenep, 2024)
This research aims to test the effectiveness of the total communication approach in improving reading skills in deaf children at Bontote'ne State Elementary School. This research uses the single subject research (SSR) method with an ABAB design. The research subject is an 11 year old boy who is currently in the 5th grade of elementary school with a hearing impairment named Muh. Jihadi.The research results show that the total communication approach is effective in improving the reading ability of deaf children. In the baseline phase, research subjects were only able to say 5 words, 25% of which were in the less capable category. In the intervention phase, research subjects were able to read words correctly 50% of the time in the quite capable category. In the advanced baseline phase, research subjects were able to read words correctly 75% of the time in the able category. In the advanced intervention phase, research subjects were able to read words correctly 85% of the time in the very capable category. Based on the results of this research, it can be concluded that the total communication approach is an effective intervention to improve the reading ability of deaf children.